Texas Rangers [videorecording (DVD)] - Rabin, Trevor (Echo Bridge Home Entertainment, 2011)
Texas Rangers: After the Civil War, Texas is at the mercy of murderous bandits. From the chaos emerges a group of young cowboys summoned to reform the Texas rangers and restore order! Under the fearless leadership of Leander McNelly, the new Rangers find themselves severely outgunned and outmanned ... but unmatched in courage and determination.